PENYELESAIAN DISHARMONI PERATURAN PERUNDANG-UNDANGAN MELALUI JALUR MEDIASI - Basuki Kurniawan; Nita Ryan Purbosari (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2022)
The conflict of norms or disharmony the rules in Indonesia is a legal problem often happen. This case is because some rules from the substance overlap betwen the rules. The Dispute of Disharmony the rules  with mediation is a perfect way from The Rule of Ministry of Law and Human Right Number 32 Year 2017 about  Procedures of dipute solving the rules with Non Litigation . With the purpose to create harmonization  the rules with mediation for product of law. This concept is born from  a problem  whereas many overlap regulation and the implication is created irregularity  law in a society. So that reducing  the existation of law as a the intergration to create harmony and compatibility  as a way to fullfill interest of the people. The implication of mediation  to solve the dishamony of rules as be setted by  Pemermenkum 2/2019 can be seen on pressing the count of rules  have conflict (ambivalensi) and be able to reducing  count of the application of judicial review will submit to Supreme Law.